Suitability of pet as an alternative for partial coarse aggregate replacement - Mohamad Allif, Mohamed (2014)
This research is conducted to determined suitability of PET as an alternative for partial coarse aggregate' replacement. In the past decade, the environmental issues have been strongly emphasized as the environmental problem is getting more severe each day.Plastic waste deserves special attention due to non-biodegradable property which makes a lot of problems in the environment. Therefore, we suggested PET as alternative for coarse aggregate replacement in order to minimize environmental problem. At the end of this research we will able to determine the suitability of PET plastic bottle as alternative coarse aggregate in concrete production, attain the structural and mechanical behaviour of PET concrete and identify the optimum strength of PET concrete as compared to conventional concrete. The tests which are used to achieve the objectives are slump test,compressive strength test, flexural strength test, and water penetration test. Different percentage of PET proportion in the concrete which are 2.5%, 5.0%, 7.5% and 10.0% was mixed out and the results of the test were compared with the conventional concrete with 0% of PET proportion. Outcomes from the test conducted shows the most suitable percentage for PET as partial replacement are 2.5% which it will gives more strength,durability and acceptable workability and water penetration depth. The reduction of the concrete strength is closely related with reduction of present of coarse aggregate in concrete mixing.